The clinical significance and potential therapeutic target of tumor-associated macrophage in non-small cell lung cancer - Sun, Jiazheng; Zhou, Sirui; Sun, Yalu; Zeng, Yulan (Frontiers in Medicine, 2025)
One of the leading causes of cancer-related mortality globally is non-small cell lung cancer (NSCLC). It has become a significant public health concern due to its rising incidence rate and fatality. Tumor-associated macrophage (TAM) is important in the tumor microenvironment (TME) of NSCLC because they have an impact on the development, metastasis, and incidence of tumors. As a crucial element of the TME, TAM contributes to tumor immune evasion, facilitates tumor proliferation and metastasis, and modulates tumor angiogenesis, immunosuppression, and treatment resistance through the secretion of diverse cytokines, chemokines, and growth factors. Consequently, TAM assumes a multifaceted and intricate function in the onset, progression, and therapeutic response of NSCLC, serving as a crucial focal point for comprehending the tumor microenvironment and formulating novel therapeutic methods. The study aims to review the biological properties and potential processes of TAM in NSCLC, investigate its involvement in the clinical of NSCLC patients, and discuss its potential as a therapeutic target.